Are fiscal adjustments less successful in decentralized governments? - Schaltegger, Christoph A.; Feld, Lars P. (CESifo working papers, 2007)
A common political claim is that decentralized governments undermine policy makers' ability to fight fiscal imbalance. This paper examines how different fiscal institutions influence the likelihood of a successful fiscal adjustment. Using a panel of the Swiss cantons from 1981 to 2001, we first analyze the episodes of tight fiscal policy and their macroeconomic consequences. Then, we empirically investigate the determinants of successful long-lasting deficit reductions. Contrary to the popular claim, we find that fiscal decentralization increases the probability of a successful fiscal consolidation. In addition, the results point to an important role of intergovernmental grants and the circumstances, in particular the size of fiscal imbalance in the years before the consolidation in determining a successful adjustment policy. Furthermore, coalition governments and large parliaments less likely implement successful fiscal stabilizations. Finally, there is some weak evidence that spending cuts are more promising in reaching a long-lasting fiscal adjustment than revenue increases.
Literaturverz
Keywords: 1981-2001; Makroökonomisches Modell; Konsolidierung; Steuerharmonisierung; Föderalismus; Schweiz